House Prices, Capital Inflows and Macroprudential Policy - Caterina Mendicino; Maria Teresa Punzi (Kiel University, FinMaP - Financial Distortions and Macroeconomic Performance, 2014)
This paper evaluates the monetary and macroprudential policies that mitigate the procyclicality arising from the interlinkage4s between current account deficits and financial vulnerabilities. We develop a two-country dynamic stochastic general equilibrium (DSGE) model with heterogeneous households and collateralised debt. The model predicts that external shocks are important in driving current account deficits that are coupled with run-ups in house prices and household dept. In this context, optimal policy features an interestrate response to credit and a LTV ration that countercyclically responds to house price dynamics. By allowing an interest-rate response to changes in financial variables, the monetary policy authority improves social welfare, because of the large welfare gains accrued to the savers. The additional use of a countercyclical LTV ratio that responds to house prices, increases the ability of borrowers to smooth consumption over the cycle and is Pareto improving. Domestic and foreign shocks account for a similar fraction of the welfare gains delivered by such a policy.
info:eu-repo/grantAgreement/EC/FP7/612955
Keywords: C33; E51; F32; G21; 330; house prices; financial frictions; global imbalances; saving glut; dynamic loan-to value ratios; monetary policy; optimized simple rules